2021
DOI: 10.15252/embr.202051041
|View full text |Cite
|
Sign up to set email alerts
|

POGZ promotes homology‐directed DNA repair in an HP1‐dependent manner

Abstract: The heterochromatin protein HP1 plays a central role in the maintenance of genome stability but little is known about how HP1 is controlled. Here, we show that the zinc finger protein POGZ promotes the presence of HP1 at DNA double-strand breaks (DSBs) in human cells. POGZ depletion delays the resolution of DSBs and sensitizes cells to different DNA-damaging agents, including cisplatin and talazoparib. Mechanistically, POGZ promotes homology-directed DNA repair by retaining the BRCA1/BARD1 complex at DSBs in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
(145 reference statements)
0
12
0
Order By: Relevance
“…To confirm and extend these studies, we next evaluated the POGZ subunit of this complex. A recent report indicated that POGZ also functions in HR repair ( Heath et al, 2021 ). Consistent with this report, knockdown of POGZ, like knockout of CHAMP1, resulted in decreased DSB end resection, decreased RAD51 foci, and increased PARPi sensitivity, consistent with a decrease in HR activity ( Figures 7A – 7C , S7A , and S7B ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm and extend these studies, we next evaluated the POGZ subunit of this complex. A recent report indicated that POGZ also functions in HR repair ( Heath et al, 2021 ). Consistent with this report, knockdown of POGZ, like knockout of CHAMP1, resulted in decreased DSB end resection, decreased RAD51 foci, and increased PARPi sensitivity, consistent with a decrease in HR activity ( Figures 7A – 7C , S7A , and S7B ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of MS data was conducted as described before with minor modifications 55 . Briefly, samples were injected into an Orbitrap Fusion (Thermo Fisher), and raw files were analyzed with the Comet, XTandem!…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of Annexin-V and PI signals were done on at least 30 000 events acquired on a BD Fortessa (Becton Dickinson). Data were analyzed using the FlowJo software as previously described 55 .…”
Section: Apoptosismentioning
confidence: 99%
See 2 more Smart Citations